The use of a simple anal sling in the management of anal incontinence - Devesa, José Manuel (Oxford University Press, 2014)
Background. Many patients presenting with anal incontinence (AI) are frail, with attendant comorbidities precluding the use of complicated, expensive reconstructive techniques. In these cases, revisiting a simple approach—designed to provide some sort of effective barrier to stool—is worthwhile where the options include a customized peri-anal sling or the use of an anal plug. Methods. Analysis of an unselected cohort of 33 patients (mean age 54 years; range 27–86 years) with AI is presented, these patients having undergone insertion of an elastic band peri-anal sling between December 2004 and December 2009. Pre- and post-operative assessment included the Jorge-Wexner score of incontinence, anorectal manometry and the Rockwood Fecal Incontinence Quality of Life (FIQoL) score. Results. The follow-up period ranged from 50 to 108 months with a mean of 65 months. Early post-operative complications included spontaneous disruption of the sling at the fourth and seventh post-operative day in two patients and local infection in a further two cases. Late complications included skin erosion in two patients, (one occurring 3 years post-operatively) and breakage of the sling in a further seven patients. Explantation was performed in 13 cases, and re-implantation in 10 patients. No differences were noted in resting or squeeze manometry, with significant improvement in the Jorge-Wexner scores in 32 cases and in all of the four Rockwood quality of life scales. Conclusions. An anal sling is an effective and simple surgical option for the management of selected cases presenting with anal incontinence. Longer-term data are awaited comparing this technique with other standard surgical alternatives.